PROMOTING MATHEMATICAL JUSTIFICATION THROUGH REALISTIC MATHEMATICS EDUCATION CLASSROOM - Sarumaha, Yenny Anggreini; Rizkianto, Ilham (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
The importance of mathematical justification in all classrooms is emphasized by reform movements in mathematics education. However, previous studies reveal that encouraging justification in mathematics classes is troblesome for mathematics teachers at all school levels. This present study is aimed to find out how justification help students to develop their mathematical understandings. To answer this question, we first determined the role of justification in teaching and learning process and how good students in justifying their answers. Design research was chosen as an appropriate mean to achive that goal. The study was conducted in a state university in Yogyakarta involving four students from fifty-one students as our focus group and one of researchers as a lecturer. Justification was the focus on this study and to promote it we chose RME as an approach that served as a learning environment. In this study, all data collected from classroom observation, group observation, students’ works, video recordings, field notes during teaching experiment, and students’ final writen test. Students’ works then analyzed using a justification rubric and describe thoroughly by considering other data collected during teaching learning process. The study revealed that there were some roles of justification in RME classroom, namely encouraged conceptual understanding, supported mathematical skill, promoted long lasting skill, and influenced social relationship. In this study, most students in our focus group have already made a good justification which was assessed by the points in the CLEAR rubric. Students wrote their solutions equipped by signs or simbols, made labels, used a complete sentence to answer the question, and elaborated procedures throroughly